Pengaruh Waktu Tinggal Hidrolik Terhadap Penyisihan Padatan Pada Pengolahan Sludge Ipal Pulp And Paper Menggunakan Bioeraktor Hibrid Anaerobik - Ardian, Siti; Ahmad, Adrianto; Herman, Syamsu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The increasing of pulp and paper industry in Indonesia had brought environmental problems which caused by Sludge waste pollution. The characteristic the wastewater treatment of pulp and paper sludge includes TS (Total Solid) 7.6 gr/L; TVS (Total Volatile Solid) 7,4 gr/L; TSS (Total Suspended Solid) 6,0 gr/L; and VSS (Volatile Suspended Solid) 5,9 gr/L. The impact will potential if the solid contents were threw away into the water because the materials of the solid containts can became pollute in environtment. This research with treat the wastewater treatment of pulp and paperâs sludge using a hybrid anaerobic bioreactor with stoned-media to see the effect of hydraulic retention time 5, 4, 3, 2, and 1 days. The results of this research showed that the longer of hydraulic retention time is given, then the greater of solid elimination efficiency. The highest solids elimination efficiency can be found on hydraulic retention time 5 days. The value of TS (44.03%), TVS (83.06%), TSS (68.85%), and VSS (95.25%). The performance by hybrid anaerobic in wastewater treatment sludge has been good, in lowering the solids content parameters.Keywords: anaerob; efficiency; hybrid bioreactor; hydraulic retention time